Readiness Analysis of Hospital Management Information System Implementation using COBIT 5 Framework - Talsi Transino; Ifmaily Ifmaily; Husna Yetti (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2021)
Every hospital has to implement Hospital Management Information System (HMIS) based on Permenkes No. 82 Tahun 2013. Health care delivery can be more effective and efficient through HMIS implementation. RSUD Solok Selatan has planned to implement HMIS since 2019 until recently. The purpose of this study is to know the readiness of HMIS implementation in RSUD Solok Selatan using COBIT 5 Framework, specifically APO02 process (strategic management), APO07 (human resource management), and APO12 (risk management). This study was conducted with qualitative-quantitative approach. Qualitative data was collected with an interview. Meanwhile, quantitative data was collected with questionnaire according to COBIT 5 Framework. Respondents of this study was determined by RACI chart in COBIT 5. Capability level of APO02 achieved level 0, based on the level 1 assessment was 2,48 (not achieved). The capability level of APO07 was level 0 and level 1 assessment was 1,25 (partially achieved). Capability level of APO12 was level 0 and level 1 assessment was 1,0 (not achieved). Level 0 indicated that COBIT 5 was non implemented or the process fails to achieve its outcome. Readiness in strategic management, human resource management, and risk management was not optimally planned. RSUD Solok Selatan needs to increase its capability to plan HMIS implementation for better output.